2020
DOI: 10.1109/taslp.2020.2969845
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Band-Limited Decorrelation Between Vertically Oriented Loudspeakers

Abstract: Two experiments have been conducted to investigate the perceptual effect of band-limited interchannel decorrelation between vertically oriented loudspeakers. The perceived vertical image spread (VIS) and tonal quality (TQ) of phantom auditory images have been subjectively assessed in multiple comparison trials. The aim of the article was to find a lower decorrelation boundary that provides a significant increase of VIS, whilst maintaining TQ close to that of the original source. For test stimuli, decorrelation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, the other vertical pairs of PCMA-3D (FL-FRh, FL-RLh, and FL-RRh) still had at least 1-m spacing between the microphones and therefore their ICCs were comparable to those of the other spaced main arrays in general. Gribben and Lee [61,62] found that in a nine-channel loudspeaker reproduction, the effect of vertical ICC on vertical image spread (VIS) was largely insignificant for low frequencies but significant for frequencies above about 1 kHz, albeit only slight. The current results show that the ICCs of the vertical pairs for all of the spaced arrays apart from PCMA-3D were very low (about 0.1 or below) for the middle and high frequency bands.…”
Section: Interchannel Correlation Coefficient (Icc)mentioning
confidence: 99%
“…On the other hand, the other vertical pairs of PCMA-3D (FL-FRh, FL-RLh, and FL-RRh) still had at least 1-m spacing between the microphones and therefore their ICCs were comparable to those of the other spaced main arrays in general. Gribben and Lee [61,62] found that in a nine-channel loudspeaker reproduction, the effect of vertical ICC on vertical image spread (VIS) was largely insignificant for low frequencies but significant for frequencies above about 1 kHz, albeit only slight. The current results show that the ICCs of the vertical pairs for all of the spaced arrays apart from PCMA-3D were very low (about 0.1 or below) for the middle and high frequency bands.…”
Section: Interchannel Correlation Coefficient (Icc)mentioning
confidence: 99%
“…For the opposite direction let us assume, there exists diagonal matrix P satisfying (23). Thus, A J is diagonally similar to pV {Dq -1 .…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…Both SISO and MIMO allpass FDNs were applied to a wide range of roles including: 1) increasing the echo density as preprocessing to an artificial reverberator [2,16]; 2) increasing echo density of in the feedback loop of reverberators [17][18][19][20]; 3) decorrelation for widening the auditory image of a sound source [21][22][23]; 4) as reverberator in electro-acoustic reverberation enhancement systems [15,18,24,25]; 5) linear dynamic range reduction [26,27] ; and 6) dispersive system design [28][29][30]. In the broader context of control theory, allpass FDNs are strongly related to Schur diagonal stability [31], e.g., stability properties of asynchronous networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For blanket reduction, the median thresholds that were derived in [9] were used (i.e., −9.5 dB for 0 ms and −7 dB for 1 ms). The 0 ms condition is equivalent to a vertical coincident microphone configuration [26], whereas the 1 ms condition represents the spacing between the main and height microphones being 0.34 m. This would be a practical spacing for a 3D microphone array, since, beyond this spacing, there would be no perceived increase in vertical image spread and the tonal quality would decrease [27]. In addition, the author's previous study on the VLT while using the same sound sources also tested the ICTD of 10 ms, but there was no significant difference found between 1 ms and 10 ms in the results.…”
mentioning
confidence: 99%